Writing about music - Wingell, Richard (Pearson Prentice Hall, 2009)
How do you put into the words the experience of hearing Beethoven's Ninth or the Hallelujah Chorus? Describe a John Coltrane solo or the Jimi Hendrix's blazing guitar work? For many students, the task of writing about musical experiences is a daunting one. Writing About Music, 4th edition offers practical advice and guidance to help students master the special skills needed to write about this most-elusive of arts. The text serves as a guide for each phase in the process of researching and writing a paper on a musical topic, and preparing for other projects such as seminar presentations, concert reports, program notes and essay examinations. Innovative, comprehensive, and internet-savvy, this step-by-step text will remain on music students' shelves as a handy reference and resource for years to come [Publisher description]; Writing about music -- Analysis and research -- Getting started -- Writing a research paper -- Questions of format -- Other kinds of writing projects -- Writing style -- Common writing problems.; Includes bibliographical references and index.